No bad deed : a novel - Chavez, Heather (William Morrow, an imprint of HarperCollinsPublishers, 2020)
"For fans of Harlan Coben and Lisa Gardner, a thrilling debut about a mother desperate to find the connections between her husband who's just gone missing and a stalker who knows way too much about her own dark family history." --